Antimicrobial Efficacy and Cytocompatibility of Calcium Hypochlorite Solution as a Root Canal Irrigant: An in Vitro Investigation - Sedigh Shams, Mahdi; Gholami, Ahmad; Abbaszadegan, Abbas; Yazdanparast, Roohollah; Saberi Nejad, Milad; Safari, Azam; Nabavizadeh, Mohammadreza; Ghasemi, Younes (Iranian Endodontic Journal, 2016)
Introduction: The purpose of this study was to compare the antimicrobial efficacy of sodium hypochlorite (SH) and calcium hypochlorite (CH) against Enterococcus faecalis (E. faecalis) using quantitative real-time polymerase chain reaction (qPCR) analysis and also to compare their cytocompatibility on L929 murine fibroblasts using Mossman’s tetrazolium toxicity (MTT) assay. Methods and Materials: A broth micro-dilution susceptibility test was used to determine the minimum inhibitory concentration (MIC) of each irrigant against E. faecalis. Then, the root canals of 50 mature extracted human mandibular premolars were contaminated with E. faecalis and were randomly divided into three groups according to the irrigant used (n=20). Canals were irrigated with SH in group I (n=20) and CH in group II (n=20) at their obtained MIC. In group III (n=10), sterile saline was used. Microbial sampling was performed before and after biomechanical preparation. Quantitative PCR was used to quantify E. faecalis in the root canal samples. For cytocompatibility assessment, L929 murine fibroblasts were exposed to various concentrations of the irrigants. Results: Irrigation with test materials resulted in significant reduction in colony forming units (CFU) in post-instrumentation samples (with the MIC values of SH and CH against E. faecalis being 0.5% and 5%, respectively). However, the reduction in the normal saline group was not significant (P=0.203). In addition, 5% CH was more effective than 0.5% SH (P=0.006) in eliminating E. faecalis. Among the different concentrations of tested irrigants, 0.5% CH and 5% SH showed the least and the most cytotoxicity, respectively (P<0.001). The cytotoxicity of 5% CH and 0.5% SH was similar (P=0.99), and lower than 2.5% SH (P<0.001). Conclusion: CH at an MIC of 5% was effective in eliminating E. faecalis in planktonic state and also its biofilm and exhibited comparable cytocompatibility to that of 0.5% SH. Keywords: Calcium Hypochlorite; Enterococcus faecalis; Polymerase Chain Reaction; Root Canal Irrigant; Sodium Hypochlorite